Mercy, happiness and human growth in the teaching of Pope Francis - Lam, Joseph C. Quy (The Australasian Catholic record, 2016)
On 11 April 2015 Pope Francis called for a special of Year of Mercy, which subsequently was symbolically inaugurated with the opening of the Holy Doors of the Basilicas of St Peter and of St John in Rome on 8 December. According to the Argentinian Pontiff, upon whose episcopal ministry is placed the maxim miserendo atque eligendo, mercy is the key element leading to the rediscovery of the spiritual joy that appears to have faded away in the life of the church. To counter this pessimism, Francis reminds his flock of the affectionate and tenderhearted look of God, whose merciful and loving gaze enriches and liberates the life of every Christian: "Thanks solely to this encounter or renewed encounter with God's love, which blossoms into an enriching friendship, we are liberated from our narrowness and self-absorption". Yet, Francis in his major teaching documents seems to caution against the concept of happiness, even though his description of the effects produced by the mercy and joy of the Gospel leads to human growth, within which human happiness is understood as a right. He has called for an integral development that includes society's most neglected members,6 and that respects and includes all forms of existence. Nonetheless, it is not a soft choice, as if mercy opens the door to all forms of pleasure as long as they make people happy.